Dieta de una especie nueva de Piabucina (Pisces: Lebiasinidae) en Alto Cauca, Colombia - Román-Valencia, César (Universidad de Costa Rica, 1997)
The diet of an undeseribed speeies of the fish genus Piabucina in the Viejariver basin, upper Cauea, Colombia, was assessed on the basis of 1I5 stomachs eolleeted from June 1990 through June 1995. It feeds mainly on insects: Coleoptera, Díptera (Chironomidae and Simulidae ) and Hymenoptera (Forrnicidae).